Stress Related Physiological Changes in Cattle Brought for Slaughter - Nigil Mathew (Department of Physiology, College of Veterinary and Animal Sciences, 2002)
The study was conducted in adult female cattle with an average body weight of about 250 kg which were transported for slaughter to Meat Technology Unit (MTU), College of Veterinary and Animal Sciences, Mannuthy, to evaluate the effect of transport stress on certain physiological \ parameters. Group I animals comprised of 12 numbers, of which six animals each were transported from Livestock Research Station (LRS), Thiruvazhamkunnu and Cattle Breeding Farm (CBF), Thumburmuzhi and they were designated as the low density stocking group (LDS) given a floor space allowance of 1.88 m2/animal. Eight adult female cattle brought for slaughter by trucking at Corporation slaughter house, Thrissur which were given with a floor space allowance of 0.95 m2/animal formed the Group Il or high density stocking group (HDS) and eight adult female cattle brought for slaughter from University Livestock Farm, Mannuthy by walk formed the Group III category . . Body weight was recorded in LDS group cattle (group I) before and after the journey and it was observed that the percentage reduction in live weight was 2.18 per cent which was not that much appreciable due to the ideal transporting conditions provided for them. Blood samples were collected with and without anticoagulant (1) before transport, (2) immediately after the journey (zero hour post-transport) and (3) after a resting period of 18 h from LDS cattle. From HDS group, immediately after unloading (zero hour post- transport) and after 18 h of rest blood collections were done. Blood samples,